Do young people know ASEAN? update of a ten-nation survey - Thompson, Eric C.; Chulanee Thianthai 1974-; Moe Thuzar (ISEAS Yusof Ishak Institute, 2016)
In 2007, a survey - the first of its kind - was carried out to gauge young people's awareness of and attitudes towards ASEAN, following the decision by ASEAN heads of state and government to accelerate the date for accomplishing an integrated ASEAN Community by 2015. Views and attitudes from university undergraduates in the ten ASEAN member states who participated in the survey indicated a nascent sense of identification as citizens of the region as well as their priorities for important aspects of regional integration. An update to the 2007 survey was carried out in 2014-15 among the same target population but with an expanded scope of twenty-two universities and institutes of higher learning across the ten member states. In the updated survey, we found that there are more ASEAN-positive attitudes region-wide, but there are also increases in ASEAN-ambivalent attitudes at country-level in some ASEAN members. Young people's priorities for important aspects of regional integration have also shifted away from economic cooperation to tourism and development cooperation. New questions in the latest survey also allow us to demonstrate the descriptive vocabulary and cognitive maps students hold for the region and its nations. This book details the key findings of the updated survey compared to the earlier survey. These include nation-by-nation results and a summary of region-wide trends, as well as what they suggest for the prospects of ASEAN integration beyond 2015. These are assessed in a chapter providing broad recommendations for policymakers and educators in the ASEAN member states.